Job Market Mapping of Library Workers in Indonesia: 2019-2024 - Irfaniah, Hikmah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The growing number of Library and Information Science (LIS) Study Program in Indonesia have resulted in the surge of graduates in this field. To ensure the link and match between labor demand and graduate qualification, job market demands need to be identified. This study aims to identify the job market qualifications based on demographic characteristics requirements, soft skills requirements, and hard skills requirements. Quantitative content analysis is employed to measure the frequency of requirements occurs on the job advertisements. 390 advertisements shared in “Lowongan Kerja Pustakawan” and “Lowongan Pustakawan” Facebook accounts from 2019-2024 are analyzed. This study involves two coders to ensure the finding reliable. The results shows that most position did not require specific demographic characteristics, except education background. The most required soft skills are collaboration and communication. Meanwhile, language, collection management, ICT skills are required hard skills of library workers. This research contributes to providing important information to library science study programs in enabling their graduates to have qualifications that meet the job market.